PELATIHAN PEMANFAATAN LIMBAH SEDOTAN AQUA GELAS UNTUK PEMBELAJARAN MUATAN LOKAL BAGI GURU SMP DI KABUPATEN SLEMAN - budiastuti, dkk, emy (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2009)
Abstract The Purpose of which wish to be reached through of PPM activity in the form of applying activity of Sains and technology, be as follows : 1) Gives knowledge to teacher of Junior High School in choosing study of on PKK 2) Gives information to the teacher about limitation way to overcome of supporting facilities for clan infrastructure in study of Skill Education on PKK, 3) Gives knowledge to the teacher about way of exploiting the beverage industrial disposal around the school, 4) Trains skill of teacher makes multifarious of lenan household by exploiting waste industry beverage, such as: Toper, tablecloth, etc This Training activity was done in Cloth Lab of PTBB FT UNY on 24 July 2008 until 14 August 2008. The Participant is 21 teacher’s of Junior High Scholl in Yogyakarta. Method applied in this activity are discourse, discussion - information, demonstration and experiment. They made of lenan household single form of diametrical and circle, multiple form of diametrical and circle, and lenan with various technique of “meronce”. Each participant makes four kinds of object, out of five objects planned. Based on evaluation result, this activity was attractive and its can be utilized and developed in school as component of skill teaching of PKK. And it can be to public. This Activity assessed to be very useful so that participant expects for the next activity for developing skill teaching of PKK for junior high school’s student. Training activity by participant assessed to be very useful so that they expect in order to keep activity of continuation with different topic, though still exploits waste as component of mainly. Keywords: aqua glass straw waste and skill teaching material